Safety-monitoring-type wide-range detectable contact sensor system using ultrasonic waves and viscoelastic tubing. (17th July 2016) - Jeong, Seonghee; Kanno, Shota; Kashihara, Sumito
Abstract : In physical human–robot interaction, a contact sensor is fundamentally required for robots to sense contact with humans and to take appropriate safety measures. This paper proposes a wide-range detectable contact sensor system with a safety monitoring function that uses an ultrasonic wave and a silicone rubber tube. The appropriate threshold voltage for generating a monitoring pulse signal is calculated using the estimation equation derived on the basis of the propagation characteristics of ultrasonic waves in straight and curved tubes. By comparing the periodic time between the generated monitoring signals and self-diagnostic signals, the proposed contact detection algorithm detects both contact due to tube deformation and failure of a sensor system including a stack fault. An experiment investigating the relationship between tube deformation by pushing force and the loss of peak voltage of an ultrasonic wave reveals that the sensor system can detect contact when the tube is deformed by 8 mm. Graphical Abstract: